2008
DOI: 10.1007/s11517-008-0328-9
|View full text |Cite
|
Sign up to set email alerts
|

Diameter measurement from images of fluorescent cylinders embedded in tissue

Abstract: Absorption and scattering of light by tissue as well as limitations in the resolution of the optical system influence the appearance of tissue embedded objects in fluorescence images and may reduce the accuracy of measurements from these images. Although the principles of light scattering in tissue and optical resolution are well known, the interplay between the two in fluorescence imaging in an imaging cryomicrotome is not well understood. In this paper we present and investigate an image formation model in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Recently, the point spread function has become available for the embedding medium in combination with the imaging system (22). Based on that study, the error made for the diameter values reported here was estimated.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the point spread function has become available for the embedding medium in combination with the imaging system (22). Based on that study, the error made for the diameter values reported here was estimated.…”
Section: Discussionmentioning
confidence: 97%
“…Fluorescence images are degraded due to scattering of emission light in the tissue, lens blurring, and light emanating from structures beneath the imaged surface. For the arterial cast images, image restoration entailed deconvolution with a systemspecific point spread function (12). Correction of the image stack was performed in the spatial domain using a 3D iterative deconvolution program written in CUDA (NVidia) (3).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalent way to describe the recording process is via pointspread functions (PSF) [7], which are mathematical models of how optical media blurs an imaged object. In essence, a PSF describes the response of an optically active system to a point light source, so its precise definition is that of a Green's (or impulse response) function.…”
Section: Tissue Opticsmentioning
confidence: 99%